Boganmeldelser - P. O. Träskman; Marie Indahl; Tarja Pösö; Lau Laursen; Hans Klette; Vagn Greve; Ditlev Tamm; Morten Eriksen; Ida Koch; Jørgen Dalberg-Larsen; Johan Munck; Josef Zila; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews